The Concept of Kafa'ah in Marriage (Study of Thought of Madrasah Teachers in Rejang Lebong ) - Iim Iim; Syarial Dedi; Hartini Hartini (Al-Madrasah: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
Kafa'ah in marriage is the existence of equality in position, comparable in social level, religion, lineage, and wealth. Madrasah Aliyah Negeri Rejang Lebong, a religious-based educational institution, all teachers should understand the concept of kafa'ah but in reality they have different views. Differences in interpretation regarding the understanding of the concept of kafa'ah based on the thoughts of the MAN teacher invite further interest. This study uses a qualitative approach with data sources obtained from primary data in the form of interviews with MAN Rejang Lebong teachers, and secondary data in the form of books, magazines, documents, articles, journals and websites on the internet. This study concludes that married Rejang Lebong MAN teachers consider the application of the concept of kafa'ah in the selection of prospective partners not to be the main element in the formation of a sakinah, mawaddah, warahmah family, but comfort, mutual understanding of the situation, mutual acceptance, making the family sakinah, whereas according to the opinion of unmarried MAN teachers thinks kafa'ah is something important as the main consideration in determining a life partner in order to get a sakinah, mawaddah, warahmah family, creating a quality next generation as well as eliminating gaps, and domination between spouses.Keywords: Marriage, Kafa'ah, Teacher.